The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11686-020-00332-w
|View full text |Cite
|
Sign up to set email alerts
|

Shared Makeup Cosmetics as a Route of Demodex folliculorum Infections

Abstract: Purpose The aim of the study was to examine Demodex survival in makeup cosmetics, i.e., powder cream, mascara, and lipstick, and to determine whether cosmetics shared with others can be a source of D. folliculorum infection. Methods Live D. folliculorum adults were placed in cosmetic samples and their motility was observed under a microscope. The mites were fully or partially immersed in the powder cream and lipstick, and only partially immersed in the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…With the rapid development of China's cosmetics industry, it has become the second-largest cosmetics consumer market in the world 10 . Given the target products, we selected 10 types of commonly used makeup products, including base makeup products with large areas and large amounts of use, eye makeup products that may cause eye irritation such as eyelid infection, corneal infection, dry eye syndrome, lip makeup products that may be caused by oral exposure, and cleaning and removing makeup products 4,9,[22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of China's cosmetics industry, it has become the second-largest cosmetics consumer market in the world 10 . Given the target products, we selected 10 types of commonly used makeup products, including base makeup products with large areas and large amounts of use, eye makeup products that may cause eye irritation such as eyelid infection, corneal infection, dry eye syndrome, lip makeup products that may be caused by oral exposure, and cleaning and removing makeup products 4,9,[22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Demodex survival in makeup cosmetics (powder cream, mascara, and lipstick) has been demonstrated; therefore, products used by different individuals at short intervals, from several hours to several days, can be a source of D. folliculorum infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…Demodex spp., as well as other mites, can also spread through used clothes (e.g., second-hand clothes stores, sharing clothes) [ 48 ]. In studies by Sedzikowska et al, 2021 [ 59 ], it has been also shown that sharing facial cosmetics (e.g., mascara and lipsticks) can be a source of transmission of Demodex sp. among users [ 59 ].…”
Section: Incidence Of Demodicosis In Different Patient Groupsmentioning
confidence: 99%
“…In studies by Sedzikowska et al, 2021 [ 59 ], it has been also shown that sharing facial cosmetics (e.g., mascara and lipsticks) can be a source of transmission of Demodex sp. among users [ 59 ]. Studies by Vargas-Arzola et al, 2020 [ 60 ] in a university population of over 8000 subjects showed a negative correlation with age.…”
Section: Incidence Of Demodicosis In Different Patient Groupsmentioning
confidence: 99%